A high-sensitivity, low-noise dual-band RF energy harvesting and managing system for wireless bio-potential acquisition. (October 2021) - Tian, Yuyuan; Liu, Lianxi; Ma, Jian
Abstract: This paper proposes a high-sensitivity, low-noise dual-band RF energy harvesting and managing system for wireless bio-potential acquisition. The proposed system consists of a dual-band RF energy harvester, a voltage monitor, and a power management unit (PMU). The proposed dual-band RF energy harvester adopts the hybrid threshold voltage self-compensation technology, which effectively reduces the equivalent threshold voltage of transistors and improves the power conversion efficiency (PCE). To match the input power and the load power with the minimum current consumption, a low-power voltage monitor is proposed in this paper. Moreover, the proposed PMU combines a voltage bootstrap circuit and a low-noise high-PSRR LDO to avoid the use of off-chip inductors and suppress output ripple. The proposed chip was implemented in a 0.18-μm deep n-well CMOS process, occupying a core area of 1.30 mm✕2.06 mm. The measured results show the dual-band RF energy harvester outputs a DC voltage of 1 V in two different frequency bands at the input power as low as −18.5 dBm. The PMU outputs stable DC voltages of 1 V and 1.8 V in working mode. In sleep mode, only the voltage monitor is working, and the average quiescent current is only 0.6 μA.